Learning String Transformations from Examples - Arasu, Arvind; Chaudhuri, Surajit; Kaushik, Raghav (VLDB, 2009)
"Robert" and "Bob" refer to the same first name but are textually far apart. Traditional string similarity functions do not allow a flexible way to account for such synonyms, abbreviations and aliases. Recently, string transformations have been proposed as a mechanism to make matching robust to such variations. However, in many domains, identifying an appropriate set of transformations is challenging as the space of possible transformations is large. In this paper, we investigate the problem of leveraging examples of matching strings to learn string transformations. We formulate an optimization problem where we are required to learn a concise set of transformations that explain most of the differences. We propose a greedy approximation algorithm for this NP-hard problem. Our experiments over real-life data illustrate the benefits of our approach.